Pseudofolliculitis barbae treatment: Efficacy of topical eflornithine, long‐pulsed Nd‐YAG laser versus their combination. (9th March 2021) - Shokeir, Hisham; Samy, Nevien; Taymour, Mai
Abstract: Background: Pseudofolliculitis barbae (PFB) is a chronic inflammatory disorder occurring mostly in regions of thick hair growth after shaving. PFB is characterized clinically by multiple painful, pruritic erythematous papules and, less commonly, pustules, nodules, or abscesses. Aim: To evaluate the efficacy of topical eflornithine cream only, long‐pulsed Nd‐YAG laser, versus their combination for PFB management. Patients and Methods: Overall, 40 male patients with PFB were allocated into 3 treatment groups; Group 1 (n = 12): Treated by topical eflornithine cream twice daily for 16 weeks, Group II (n = 13): Treated by long‐pulsed Nd‐YAG laser for 4 sessions 4‐week interval, Group III (n = 15): Treated by this combination for 16 weeks. The patients were evaluated after 16 weeks and for a further 12 weeks through serial photographs, Folliscopic evaluation, and a quartile grading system for improvement. Results: After 16 weeks of treatments, the mean improvement percentages of the inflammatory papules, as well as hair density in the long‐pulsed Nd‐YAG laser +eflornithine cream, treated group were significantly higher compared with either eflornithine cream treated group or laser‐only treated group. The same relationship was demonstrated after 12 weeks of follow‐up but with lower improvements compared with 16 weeks of treatment outcome. Conclusions: Topical eflornithine cream exerts an additive effect on long‐pulsed Nd‐YAG laser in enhancing the rate and degree of hair reduction and inflammatory papules in PFB cases with a further follow‐up improvement. This combined approach should be long‐established in larger sample sizes and long‐term studies.